Estimation of the Air Emissions of Pollutants Influence on Primary Morbidity Indicator of the Population : Case in Kharkiv Region – Ukraine - Nekos, A. N.; Muromtseva, Yu. I. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2021)
Purpose. To establish structural shifts in the indicators of the primary morbidity of the population, and to determine the relationship between the indicators of emissions of pollutants into the air and the primary morbidity of the population of the Kharkiv region. Methods. We used system approach, statistical methods. Results. The structure and dynamics of the number of newly registered cases of diseases and primary morbidity of the population were considered during the period from 2004 to 2017. A correlation-regression analysis of the relationships between emissions and primary morbidity by disease classes in the Kharkiv region was made, which showed the presence of a moderate correlation between the phenomena. The synthesized regression equations can be used to determine the influence of each individual factor (SO2, CO2, N2O emissions) on the primary morbidity of the population for different classes of diseases. In the structure of primary morbidity of the population of Kharkiv region, the major share is made up of diseases of the respiratory, circulatory and nervous systems - their share increased from 49% in 2004 to 51% in 2017 year. Conclusions. The indicators of primary morbidity by diseases of the genitourinary system, nervous system, circulatory system and congenital malformations were the most sensitive to air pollutions and emission CO2 into the atmosphere. The most negative impact on the values of all classes of primary morbidity in the Kharkiv region have CO2, N2O.